Farmers’ Perception of agroforestry in the Bambou–Mingali forest massif (Congo) - Bakouetila, Gilles Freddy Mialoundama; Kindiela, Budeh Wickler Nzobadila; Mankessi, François; Mabanza, Ildevert Madel Mounkala; Scherell, Ségolen Lutterah Missengué (International Journal of Environment, Agriculture and Biotechnology, 2023)
Agroforestry offers an opportunity to enhance the value of poor ferralitic savannah soils in the Republic of Congo. The aim of the study was to analyze farmers’ perceptions of agroforestry in the Bambou–Mingali artificial forest massif. A survey was conducted among 42 farmers who had signed an exploitation contract with the National Reforestation Service (SNR). The study revealed that most of the farmers involved in agroforestry on reforested state-owned plots were adults (83%) and had received education (100%). Agri-silviculture is practiced on these plots. The SNR is responsible for preparing the land for planting forest species (for example, Acacia, Eucalyptus, pines). Weeding was the only maintenance operation carried out by all farmers. Positive factors that may lead farmers to adopt agroforestry innovations in state reforested plots include free access to land, economies of scale in the establishment of food crops, and satisfaction with the yields obtained and income earned compared to savannah areas. Acacia was the most valued forest tree among farmers. Thus, the reforested plots are an opportunity to promote agroforestry for the benefit of smallholders.